Nearly Unbiased Estimationin Dynamic Panel Data Models - Martin A. Carree (Tinbergen Institute, 2002)
This paper introduces two easy to calculate estimators with desirable properties for theautoregressive parameter in dynamic panel data models. The estimators are (nearly) unbiased andperform satisfactorily even for small samples in either the time-series or cross-section dimension.
Keywords: C23; 330; dynamic panel data; Nickell bias; bias-correction; Panelforschung; Dynamisches Modell; Bias; Theorie